Treatment options for the wet form of age-related macular degeneration—a perspective - MunkMarion R.; RückertRene (眼科学报, 2016)
Treatment of the wet form of age-related macular degeneration (wet AMD) has been revolutionized a decade ago with the introduction of vascular endothelial growth factor (VEGF) blockers that reduce neovascularization and macular edema. Two approved drugs are marketed for the treatment of wet AMD—ranibizumab and aflibercept, but there is a third drug, bevacizumab, which is widely used offlabel; a cancer drug that also blocks VEGF but was never tested in pivotal trials and never approved for ophthalmic indications including wet AMD. Similarity of bevacizumab to ranibizumab led to off-label use and even to government-sponsored studies comparison the approved ranibizumab head-to-head to the offlabel cancer drug bevacizumab in wet AMD, like the Comparison of Age-related Macular Degeneration Treatments Trials (CATT) study, discussed in this perspective paper. Recent publication of 5-year follow-up from the initial 2-year CATT study provided the occasion to discuss the similarities and differences between these two drugs and the lessons learned from the last decade of anti-VEGF therapy for wet AMD. Clinical efficacy is comparable, with an advantage for ranibizumab. Likewise, safety finding favor ranibizumab over bevacizumab in some aspects. The latest addition of approved anti-VEGF drugs for wet AMD, aflibercept, may provide even more benefit to patients. In this perspective we discuss results of CATT and other longterm follow-up and comparative studies. While all demonstrate clinical benefit of anti-VEGF, all reveal that most patients’ loose visual acuity (VA) in real-life situations over 5–7 years. This loss is based on—what we believe—significant under-treatment of wet AMD patients, due to economic or practical limitations and overestimation of perceived risks as geographic atrophy. We compare own data that showed more intensive treatment (more than twice the CATT-follow-up injections) with ranibizumab or aflibercept can maintain a sustained gain in VA in wet AMD patients after 6 years. We encourage retina specialists to treat wet AMD patients more aggressively and frequently in order to provide the maximum benefit for their patients.